A practical and easy‐to‐scale protocol for removing chlorophylls from leaf extracts - Alice Fossati; Valeria Cavalloro; Daniela Rossi; Simona Collina; Emanuela Martino (Applications in Plant Sciences)
Abstract Premise Leaf extracts are valuable sources of bioactive compounds. However, co‐extracted chlorophylls interfere with analyses, including spectroscopic and biochemical assays. Existing methods for chlorophyll removal often have limitations, including the use of hazardous solvents, low specificity, or high costs. Methods and Results A solid‐phase extraction protocol for chlorophyll removal from leaf extracts of Corylus avellana was developed using commercially available cartridges. The method requires standard equipment, can be completed within 10 minutes, and is scalable from analytical to preparative quantities. We validated this protocol across 20 taxa, demonstrating the removal of 85% of chlorophylls, successful scale up of quantities, cartridge reusability, and low solvent consumption. Conclusions Key innovations of the protocol include simplified elution steps and the possibility of multiple reuse cycles. The simplicity, sustainability, and scalability of this new protocol make it particularly valuable for high‐throughput applications and process development.